APLIKASI NAA PADA PROPAGASI KANTONG SEMAR Nepenthes adrianii Batoro, Wartono & Jebb - Wahdani, Rosa Amalia; Dwiati, Murni; Kamsinah, Kamsinah (Fakultas Biologi Universitas Jenderal Soedirman, 2022)
Nepenthes adrianii is an endemic species of Mount Slamet. The existence of this species has begun to be threatened. This situation encourages efforts to conserve N. adrianii, which is through propagation using stem cuttings of N. adrianii. In order for the propagation of stem cuttings to grow properly, it is necessary to add growth hormone (ZPT) from the auxin group such as NAA (Napthalene Acetic Acid). This research has been conducted to study the effect of NAA and its effective consentration for the growth of N. adrianiistem cuttings. This research was conducted using experimental methods. The experimental design used was a Randomized Completely Block Design (RCBD). The block in this study is total leaves per cuttings. Block 1 is the leafless cuttings, block 2 is cuttings with one leaf, block 3 is cuttings with two leaves, and block 4 is cuttings with three leaves. The NAA concentrations in this study are 0, 5, 10, 15, 20, and 25 ppm. There are a total of 24 experimental units. The variable observed was the growth of N. adrianii stem cuttings. Parameters observed in this study are days taken for sprouting, number of shoots, number of leaves, leaf length, and leaf width. The results were analyzed using Variety Analysis and then analyzed with Tukey's test at the test level of 0.05 at the time of significant treatment. The results showed that the application of NAA did not affect the growth of the stem cuttings of N. adrianii. The best concentration of NAA could not be determined because there was no effect of NAA on the growth of N. adrianii stem cuttings.